1992
DOI: 10.1007/bf02777752
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 enhances hepatic portal venous flow by dilating the portal vascular bed in 70% hepatectomized dog

Abstract: The effects of portal, hepatic arterial and femoral venous administration of prostaglandin E1 (PGE) on portal venous flow (PVF) and hepatic arterial flow HAF were examined before and after 70% hepatectomy in anesthetized dogs. In the hepatectomized condition, portal venous administration of PGE (0.5 microgram/kg/min) caused an increase in PVF without any change in systemic arterial pressure (SAP). HAF was unchanged following the injection. The portal effect of PGE on PVF was dose-dependent, and a reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Those results in rats were consistent with studies that showed the effect of PGE 1 on hepatic IRI [174] followed by partial hepatectomy in dogs [175] with noncirrhotic livers.…”
Section: (D) Prostaglandins and Liver Haemodynamicssupporting
confidence: 93%
See 2 more Smart Citations
“…Those results in rats were consistent with studies that showed the effect of PGE 1 on hepatic IRI [174] followed by partial hepatectomy in dogs [175] with noncirrhotic livers.…”
Section: (D) Prostaglandins and Liver Haemodynamicssupporting
confidence: 93%
“…PGE 1 significantly improved portal venous flow (PVF) and peripheral liver tissue blood flow (TBF) after reperfusion [177]. A similar effect was also observed in some other studies which showed on IR injury [174] and partial hepatectomy [175] individually, whereas our model was a combined one of both ischemia and hepatectomy [177].…”
Section: (D) Prostaglandins and Liver Haemodynamicssupporting
confidence: 87%
See 1 more Smart Citation
“…In most of the above‐mentioned and other cases, PGE 1 was administered intravenously. However, it was confirmed that intraportal administration of PGE 1 showed the greatest protective effects against hepatic warm ischemia and reperfusion injury,21 and against partial hepatectomy22 in dogs.…”
Section: Introductionmentioning
confidence: 89%
“…The protective mechanism of PGE 1 against warm ischemia reperfusion injury of the liver was primarily achieved by increasing the portal venous flow (PVF)23 as well as by reducing the production of superoxide radicals 24. Other studies reported that PGE 1 increased the PVF in dogs22 and in rats1 when the liver was partially resected. In the resected liver the PVF is increased by dilating the vascular wall in the superior mesenteric vascular bed after infusion of PGE 1 .…”
Section: Introductionmentioning
confidence: 91%